2017
DOI: 10.1108/ijdi-04-2017-0039
|View full text |Cite
|
Sign up to set email alerts
|

Loan repayment performance of clients of informal lending institutions

Abstract: Purpose The purpose of this article is to examine the effects that dynamic incentives and the borrowing histories of clients of informal lending institutions have on loan repayment performance, in particular, the extent to which multiple borrowing and progressive lending affect the repayment of loans. Design/methodology/approach The paper uses a data set of 835 borrowers drawn from an informal lending institution in Tanzania. Descriptive analysis and econometric models are used to test the developed hypothes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 27 publications
1
23
0
Order By: Relevance
“…Adverse selection is created before the transaction occurs, when selection increases the possibility of loans made to insecure borrowers a consequential undesirable (adverse) outcome (Greenbaum, Kanatas, & Venezia, 1989; Charles & Mori, 2017). On the other hand, moral hazard is a result after the transaction occurs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Adverse selection is created before the transaction occurs, when selection increases the possibility of loans made to insecure borrowers a consequential undesirable (adverse) outcome (Greenbaum, Kanatas, & Venezia, 1989; Charles & Mori, 2017). On the other hand, moral hazard is a result after the transaction occurs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…MB i is multiple-borrowing i.e. loans from different lenders measured as a binary variable equal to 1 if the borrower had borrowed from several lending institutions and 0 otherwise (Charles & Mori, 2017), and DQ i is delinquency, i.e. a dummy that takes the value of 1 for a borrower who is in arrears of at least one day on an outstanding loan at the time of the survey, and 0 otherwise (Schicks, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…They further revealed that about 71 percent of all survey respondents admitted to often face the problem of delinquency. Similarly, Charles and Mori (2017) found out that micro-borrowers in Tanzania face increased debt levels and thus an increased inability to meet their repayment obligations. Gonzalez (2008) suggested that inability to repay, or unwillingness to repay is associated with over-indebtedness in Bolivia.…”
Section: Delinquency and Over-indebtednessmentioning
confidence: 99%
See 2 more Smart Citations